Irreversible Hemichorea–Hemiballism in a Case of Nonketotic Hyperglycemia Presenting as the Initial Manifestation of Diabetes Mellitus. (5th August 2016) - Roy, Ujjawal; Das, Shyamal Kumar; Mukherjee, Adreesh; Biswas, Debsadhan; Pan, Koushik; Biswas, Atanu; Panwar, Ajay
Background: Hemichorea–hemiballism (HCHB) is a hyperkinetic movement disorder with features of both chorea and ballism occurring on the same side. Case report: We present a case of HCHB due to nonketotic hyperglycemia (NKH) that was the initial presentation of diabetes and was irreversible clinically even after 6 months of optimal blood sugar control. Discussion: Although HCHB due to hyperglycemia is a potentially reversible condition in the majority of patients, prolonged uncontrolled hyperglycemia may cause ischemic insult and persistent symptoms. Hyperglycemia should always be kept in the list of differentials while dealing with patients who are newly diagnosed with HCHB.